Densification, microstructure and mechanical properties of Mullite–TiC composites prepared by spark plasma sintering. Issue 2 (March 2015) - Ghahremani, D.; Ebadzadeh, T.; Maghsodipour, A.
Abstract: Mullite–TiC composites were prepared using Mullite and TiC powders by spark plasma sintering at a temperature range of 1500–1600 °C for a holding time of 600 s under the pressure of 20 MPa. Microstructure, strength and hardness of the Mullite–TiC composites were studied. The Mullite–TiC composite containing 10–30 wt% TiC reached over 95% theoretical density at 1550 °C and nearly full density at 1600 °C. The strength and Vickers hardness of Mullite–(10 wt%)TiC composite sintered at 1600 °C reached a maximum value of 274 MPa and 1355 HV, respectively. Novel dense Mullite–TiC composites were fabricated by a Spark plasma sintering process. It was found out that introduction of TiC can enhance the mechanical properties of Mullite matrix effectively.